Detection of plant parasitic nematodes in the soil of crop field in Meiktila area, Myanmar - Myint, Ni Ni; Aye, Yu Yu; Aung, Yu Yu; Bawm, Saw (Journal of Scientific Agriculture, 2017)
The occurrence of soil nematodes from groundnut and chilli crop fields were investigated during the period from November 2013 to February 2014. From the collected soil samples, 13 genera belonging to seven families of three orders under two classes were recorded. Among the observed genera, Meloidogyene, was found to be the predominant on the soil samples of both groundnut and chilli crop fields. Moreover, Meloidogyene, Heterodera and Helicotylenchus were found with prominent values of 138, 92 and 85, respectively and occurred in 16%, 11% and 10% of all soil samples, respectively. Paratrichodorus was found to be the lowest in numbers 27 (3%). The data from recent study indicated that the soil samples of groundnut crop field showed higher incidence of nematodes (57%) than that of chilli crop field (43%).